Mobilizing private investment for road transport in public–private partnership: A study of influencing factors in Vietnam - Lam, Mai Dinh (Asian Development Policy Review, 2025)
This study investigates the factors influencing private sector engagement in public–private partnerships (PPPs) in Vietnam’s road transport infrastructure sector. The study employs a mixed-method approach, involving qualitative interviews with nine experts and a survey of 200 stakeholders, including government officials, financial institutions, private firms, and academic professionals. Cronbach’s Alpha, exploratory factor analysis, confirmatory factor analysis, and the relative importance index were applied to test and rank the importance of factors. The findings show that a stable socio-economic environment, firm political commitment, and a transparent legal framework are essential for successfully attracting private investment. Institutional capacity, effective risk-sharing mechanisms, and facilitative policy incentives also significantly influence private sector decisions. Private sector financial availability and access to adequate capital were also highlighted as key factors. Additionally, active supervision, stakeholder feedback mechanisms, and community engagement significantly enhance project effectiveness and encourage social acceptance. This study offers meaningful insights for evidence-based strategies that can be used to build conducive and attractive PPP investment environments in Vietnam’s road transport infrastructure sector.